Nanogenerators and Self-Powered Systems - Dudem, Bhaskar; Venkateswaran, Vivekananthan; Chandrasekhar, Arunkumar (IntechOpen, 2023)
This Edited Volume "Nanogenerators and Self-Powered Systems" is a collection of reviewed and relevant research chapters, offering a comprehensive overview of recent developments in the field of nanotechnology and nanomaterials. The book comprises single chapters authored by various researchers and edited by an expert active in harnessing the ubiquitously available biomechanical energies to power portable electronics research area. All chapters are complete in themselves but united under a common research study topic. This publication aims at providing a thorough overview of the latest research efforts by international authors on nanotechnology and nanomaterials and opening new possible research paths for further novel developments.